Analysis of the EPSRC Principles of Robotics in regard to key research topics. Issue 3 (3rd July 2017) - Gning, A.; Davis, D. N.; Cheng, Y.; Robinson, P.
ABSTRACT: In this paper, we review the five rules published in EPSRC Principles of Robotics with a specific focus on future robotics research topics. It is demonstrated through a pictorial representation of the five rules that these rules are questionably not sufficient, overlapping and not explicitly reflecting the true challenges of robotics ethics in relation to the future of robotics research.